Sistem Informasi Pendaftaran Peserta KB Berbasis Web Pada Kantor Dinas Pengendalian Penduduk Dan Keluarga Berencana Kabupaten Muaro Jambi - Ristio Ritonga, Dika; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2023)
Family planning is one of the efforts to realize family happiness and prosperity. The main goal of family planning is to further improve the well-being of mothers and children. By arranging the birth of a wife or pregnant woman so that many have the opportunity to pay attention and educate children in addition to having sufficient time to carry out activities as housewives. Children will get enough attention from parents which later can have a positive impact on the growth and development of the child's personality. Usually the registration of family planning participants is still recorded on the registration sheet so that in an effort to process the registration data for family planning participants it still takes a relatively long time. The design of a web-based family planning participant registration information system using a prototype method creates a more effective and efficient performance for people who want to register for the installation of contraceptives.